Development of Test Procedure For CMOS Operational Amplifier Application Circuits - Abdul Halin, Izhal (2002)
The integrated circuit (IC) is an ultra-small and fragile electrical system. A chip is basically an IC placed in a protective black plastic casing. The only contact the outside world has with the IC is through the chips input-output and power supply pins. ICs are also prone to damage and to locate damages inside a chip requires special probing techniques. These techniques are incorporated from the beginning of the design stage of a chip. Design for Testability (DFT) is a method applied to the design stage of chips such that electrical testing of the chips at the end of the production stage is greatly simplified. For a chip manufacturer, DFT helps cut production cost by shortening the time to test finished chips w hich eventually decreases the time to market the chip. Built-In Self Test (BIST) chips, an outcome of DFT, are ICs designed with extended circuitry dedicated to test its electrical behavior which eventually could inform a manufacturer w here damage has occurred. The testing circuitry inside a BIST chip is complimented by a test pattern, which is a special signal that executes the actual testing. The main objective of this study is to develop a test procedure to test CMOS Operational Amplifier (Op-Amp) application circuits. The focus in the development of the testing procedure is to find a suitable test pattern. The study conducted results in the success of developing the said test procedure. The development of the test procedure is aided by a powerful computer software from Tanner Research Inc. called Tanner Tools. It is used for circuit simulation and development of a mask layout for an Op-Amp. The major findings of this thesis is that a faulty Op-Amp application circuit behaves differently from a faultless Op-Amp application circuit. From this finding a test pattern can be derived by comparing between faulty and faultless Op-Amp application circuit behavior through simulation. The only disadvantage of the test pattern is that it could only detect damages in the Op-Amp if the damages occurs only one at any given time. Thus it can be argued that in relation to DFT for an Op-Amp application circuit, it is not impossible for damages to be pin-pointed using the developed procedure.